Regulating Edible Bird's Nest (EBN) industry in Malaysia: an evaluation of the current legal framework / Lua Kok Hiyong - Lua, Kok Hiyong (2012)
This research project discussed the history of Edible Birds' Nests (EBN) industry in Malaysia, the swift and its family, EBN, fake nest, problems involving nuisance caused by the swifts, public health concerns, World Heritage Sites, nitrite contents in EBN, the guidelines issued over the years and the various statutes mainly the repealed Protection of Wild Life Act, 1 Animals Act 1953 with a specific focus on Wildlife Conservation Ace and the Garis Panduan Pembangunan Industri Burung Walit, Januari 2010 (1 GP).3 Animal Welfare Bill2012 which is pending approval in the year 2013 is also discussed. It comprehensively studied and evaluated the EBN Industry and the relevant legislation in Malaysia. It also examined to what extent the 1GP and WCA 2010 are capable of addressing and overcoming the problems faced by EBN industry and the public. More importantly, the primary aim of this pioneer research project is to evaluate the available legislation and guidelines within the current legal framework relating to the EBN swifts farming in Malaysia with a view to identifying the strengths, inadequacies and weaknesses of the current legislation in protecting and promoting edible birds' nests industry and the conservation of the edible-nest swifts. It also surveyed and the relevant federal and state laws and thereafter made suggestions and proposals to overcome and improve the areas of weaknesses identified. There are eight (8) chapters in this research project. Each chapter is devoted to a specific subject matter. The contents varied and ranged from merely providing information, statements, facts and practice involving EBN industry to carrying out a critical study of a wide range of legislation applicable to EBN.